The Effect of Motivation, Compensation, Work Discipline and Leadership on Employee Performance - Rehan Firmansa; Wiyadi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The ability of human resources is formed by the character or behavior of each employee and the company's external environment. High concern for human resource development is expected to be a way to maintain and improve quality, so that it has an impact on improving employee performance in a company. The purpose of this study was to analyze the effect of motivation, compensation, work discipline, and leadership on employee performance. This type of research is quantitative research. The population in this study were all employees of PT Dan Liris in Sukoharjo. The sampling technique used in this study uses one type of Non-Probability Sampling, namely Purposive Sampling.  The number of samples of this study were 154 respondents. this research uses primary data. The data processing method in this study is to use SPSS version 29.0 software.  The results of this study are motivation has a positive and significant effect on employee performance. Compensation has no effect on employee performance. Work discipline has a positive and significant effect on employee performance. Leadership has a positive and significant effect on employee performance.